700 The role of Impella CP in the management of malignant arrhythmias: a case of asymptomatic ventricular fibrillation. (8th December 2021) - Caminiti, Rodolfo; Colarusso, Luigi; Parlavecchio, Antonio; Vetta, Giampaolo; Mancini, Nastasia; Luzza, Francesco; Micari, Antonio; Bella, Gianluca Di; Vizzari, Giampiero; Crea, Pasquale
Abstract: Introduction: The Impella Heart Pump device (Abiomed, Danvers, MA, USA) is commonly used to provide mechanical circulatory support during high-risk percutaneous coronary intervention (PCI) and has demonstrated both efficacy and safety in patients with cardiogenic shock. Left ventricular assist devices (LVADs) alter the pathophysiological impact of ventricular arrhythmias in advanced heart failure; for example, life-threatening arrhythmias such as ventricular fibrillation (VF). We present a case of sustained VF tolerance in a patient with IMPELLA CP ® support. Methods and results: A 64-year-old man was admitted with typical chest pain that began 3 days earlier and an anterior myocardial infarction with ST-segment elevation. Urgent coronary angiogram showed a left anterior descending artery treated with angioplasty and stent implantation (TIMI 3). An initial echocardiogram, performed after PCI, showed a reduced left ventricular ejection fraction (LVEF) of approximately 35% with good right ventricular function. Two days later, the ECG tracing showed persistence of the ST elevation, and the patient developed recurrent ventricular tachycardia and an episode of acute pulmonary oedema; the echocardiogram showed a significant worsening of LVEF (15%). A percutaneous mechanical circulatory support device (Impella CP; Abiomed) was inserted through the right common femoral artery in order to preserve adequate systemic perfusion (Figure 1A). Twelve hours later, the patient developed rapid VT degenerating into VF without loss of consciousness (Figure 1C). During the arrhythmia, the patient was alert and his mental status was normal, Impella flow was 2.4–3.0 l/min, and invasive blood pressure (IBP) was 80/65 mmHg (Figure 1D). Intravenous lidocaine was administered without effect. After approximately 10 min of incessant VF, the patient received sedation with propofol from the anesthesiologist. A single unsynchronized DC shock of 200 J converted the patient to sinus rhythm. A bedside transthoracic echocardiogram was performed to check the optimal position of the Impella device (Figure 1B). In the following days, the patient had two new episodes of asymptomatic VF treated with DC-shock after sedation and was transferred to the cardiac surgery department to undergo urgent LVAD implantation. Conclusions: Impella CP was helpful in the management of this patient with severe heart failure and malignant ventricular tachyarrhythmias, reducing the hemodynamic and neurological impact of this latter catastrophic arrhythmic event.